PENGARUH LIVE STREAMING ENGAGEMENT TERHADAP CONTINOUS WATCHING INTENTION - Leiwakabessy, Abraham; Kurnia, Kurnia (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2023)
The growth of YouTube as one of the live streaming platforms is also accompanied by the rise of the video game trend that utilizes this media as a means of broadcasting game content. Dyland PROS is one of the YouTubers known as a gaming content creator streamer in Indonesia. With 16.1 million subscribers, Dyland PROS channel holds a broadcasting grade of B+. This research employs a quantitative approach. In this study, the analysis is conducted using Partial Least Square (PLS) through the stages of measurement model testing, including validity testing with a minimum outer loading value standard of 0.70 and an AVE (Average Variance Extracted) value above 0.50 to be considered valid. Reliability testing is also performed by examining the Cronbach Alpha or Composite Reliability values, with a requirement of above 0.70 to be considered reliable. Based on the results of this research, it can be concluded that Live Streaming engagement has a proven positive influence on Continuous Watching Intention. To maintain a continuous viewing intention, Live Streaming content must be able to create engagement. Engagement in live streaming content can be achieved through: (1) Content and Form Aesthetics, Communication with Others, Emotional Reactions.